Spectral asymmetry on the ball and asymptotics of the asymmetry kernel - Kirchberg, A. (2006)
Let be i∂/ the Dirac operator on a D = 2d dimensional ball B with radius R. We calculate the spectral asymmetry η(0, i∂/) for D = 2 and D = 4, when local chiral bag boundary conditions are imposed. With these boundary conditions, we also analyse the small-t asymptotics of the heat trace TrFP e−tP² where P is an operator of Dirac type and F is an auxiliary smooth smearing function.